Inorganic composition product
By controlling the content of Li2O, SiO2 and Al2O3 and forming a compressive stress layer, the problem of existing chemically reinforced glasses being easily damaged when they fall is solved, and higher mechanical strength and impact resistance are achieved.
Patent Information
- Application Number
- CN202380052070.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-15
- Filing Date
- 2023-07-13
- Publication Date
- 2025-03-14
AI Technical Summary
Existing chemically reinforced glass is prone to damage when dropped by portable devices such as smartphones, especially when dropped to a rough surface, and the fracture is not easily prevented. The center tensile stress is too high, resulting in too small fragments.
By controlling the content of Li2O, SiO2 and Al2O3 and forming a compressive stress layer on the surface, a reinforced crystallized glass with a central tensile stress between 80 MPa and 160 MPa was produced.
It achieves the effect of not being easily broken when falling to a rough surface, and at the same time avoids the small problem of fragmentation caused by excessive center tensile stress, providing higher mechanical strength and impact resistance.
Smart Images

Figure BDA0005229539630000091 
Figure BDA0005229539630000101 
Figure BDA0005229539630000111
Abstract
Description
Technical Field
[0001] The present invention relates to an inorganic composition product such as reinforced crystallized glass having a compressive stress layer on the surface. Background Art
[0002] In this field, various glasses are expected to be used as cover glasses or housings for protecting displays of portable electronic devices such as smart phones and tablet PCs (personal computers), and also as protectors for lenses of vehicle-mounted optical devices, interior frames or console panels, raw materials for touch panels, smart keys, etc. Moreover, these devices need to be used in harsh environments, which strongly requires that the glass have higher strength.
[0003] In the past, chemically strengthened glass was used as a material for protecting components. However, the existing chemically strengthened glass is often broken when a portable device such as a smartphone is dropped, which is considered a problem. In particular, crystallized glass that is not easily broken when dropped on a rough surface such as asphalt is required.
[0004] If the central tensile stress (CT [MPa]) is high, the glass fragments tend to become smaller and smaller when the glass breaks. In addition, when used as a protective component, the glass surface is sometimes ground and used, but the CT decreases when the glass surface is ground, so the CT of the glass before grinding must be increased in advance. However, in the case where there is no grinding step, there is a problem that the CT is too high, so when the glass breaks, the glass fragments become too small and become small fragments. Therefore, a glass with a CT that is not too high is sought that can cope with the situation even without the grinding step.
[0005] Patent Document 1 discloses a material composition of a crystallized glass substrate for information recording media that can be chemically strengthened. It describes that the α-white silica-based crystallized glass described in Patent Document 1 can be chemically strengthened and can be used as a material substrate with higher strength. However, crystallized glass for information recording media represented by hard disk substrates is not intended to be used in harsh environments.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2008-254984 Summary of the invention
[0009] The object of the present invention is to provide an inorganic composition product such as a strengthened crystallized glass which is not easily broken when dropped onto a rough surface. In addition, the object of the present invention is to provide an inorganic composition product such as a strengthened crystallized glass which has a CT that is not too high.
[0010] The present invention provides the following composition.
[0011] (Composition 1)
[0012] An inorganic composition product is obtained by strengthening crystallized glass, wherein the crystallized glass contains one or more selected from α-white silica and α-white silica solid solution as the main crystalline phase, and the mass % converted into oxides is:
[0013] The content of SiO2 component is 50.0% to 75.0%;
[0014] The content of Li2O component is 3.0% to 10.0%;
[0015] The content of Al2O3 component is 5.0% or more and less than 15.0%;
[0016] The content of B2O3 component is greater than 0% and less than 10.0%;
[0017] The content of P2O5 component is greater than 0% and less than 10.0%; and
[0018] The mass ratio SiO2 / (B2O3+Li2O) is 3.0 to 10.0; and
[0019] The inorganic composition product has a compressive stress layer on the surface; and the central tensile stress (CT) is 80 MPa to 160 MPa.
[0020] (Composition 2)
[0021] The inorganic composition product as described in composition 1, wherein:
[0022] The crystallized glass is calculated in terms of mass % of oxides:
[0023] The content of ZrO2 component is greater than 0% and less than 10.0%;
[0024] The total content of Al2O3 and ZrO2 components is 10.0% or more.
[0025] (Composition 3)
[0026] The inorganic composition product as described in Composition 1 or Composition 2, wherein:
[0027] The crystallized glass is calculated in terms of mass % of oxides:
[0028] The content of K2O component is 0% to 5.0%.
[0029] (Composition 4)
[0030] The inorganic composition product as described in any one of Compositions 1 to 3, wherein:
[0031] The crystallized glass is calculated in terms of mass % of oxides:
[0032] The content of Na2O component is 0% to 4.0%;
[0033] The content of MgO component is 0% to 4.0%;
[0034] The content of CaO component is 0% to 4.0%;
[0035] The content of SrO component is 0% to 4.0%;
[0036] The content of BaO component is 0% to 5.0%;
[0037] The content of ZnO component is 0% to 10.0%;
[0038] The content of Sb2O3 component is 0% to 3.0%.
[0039] (Composition 5)
[0040] The inorganic composition product as described in any one of Compositions 1 to 4, wherein:
[0041] The crystallized glass is calculated in terms of mass % of oxides:
[0042] The content of Nb2O5 component is 0% to 5.0%;
[0043] The content of Ta2O5 component is 0% to 6.0%;
[0044] The content of the TiO2 component is 0% or more and less than 1.0%.
[0045] (Composition 6)
[0046] The inorganic composition product as described in any one of Compositions 1 to 5, wherein:
[0047] The glass transition temperature (Tg) of the crystallized glass before crystallization is 610° C. or less.
[0048] (Composition 7)
[0049] The inorganic composition product as described in any one of Compositions 1 to 6, wherein:
[0050] The crystallized glass is chemically strengthened by using a salt bath containing lithium.
[0051] According to the present invention, by controlling the amount of Li2O and adjusting the amount of SiO2 and Al2O3, it is easy to manufacture and stably manufacture an inorganic composition product such as a reinforced crystallized glass that is not easily broken when dropped onto a rough surface. In addition, according to the present invention, an inorganic composition product whose CT is not too high can be provided.
[0052] The "inorganic composition product" in the present invention is composed of inorganic composition materials such as glass, crystallized glass, ceramics or their composite materials. For example, products obtained by processing these inorganic materials or synthesizing them by chemical reactions to form them into desired shapes are in line with the products of the present invention. In addition, compressed powders obtained by crushing inorganic materials and pressurizing them, or sintered bodies obtained by sintering compressed powders, etc. are also in line with the present invention. The smoothness, curvature, size, etc. of the shape of the product thus obtained are not limited. For example, it is a plate-like substrate, a molded body with curvature, or a three-dimensional structure with a complex shape. In addition, products obtained by chemically strengthening inorganic composition materials are also in line with the present invention.
[0053] The inorganic composition product of the present invention can be used as a protective component of equipment by making full use of the characteristics of being a glass-based material with high strength and processability. It can be used as a cover glass or housing of a smartphone, a component of a portable electronic device such as a tablet PC or a wearable terminal, or a component such as a protective protector or a substrate for a head-up display used in a transport body such as a vehicle or an airplane. In addition, it can also be used for other electronic devices or mechanical appliances, building components, components for solar panels, components for projectors, cover glass (windshield) for glasses or clocks, etc. DETAILED DESCRIPTION
[0054] Hereinafter, the embodiments and examples of the inorganic composition product of the present invention will be described in detail, but the present invention is not limited to the following embodiments and examples and can be implemented with appropriate changes within the scope of the purpose of the present invention.
[0055] The crystallized glass used as the base material in the present invention contains one or more selected from α-cristobalite and α-cristobalite solid solution as the main crystal phase. The crystallized glass in which these crystal phases are precipitated has high mechanical strength.
[0056] Here, the "main crystalline phase" in this specification corresponds to the crystalline phase with the largest content in the crystallized glass determined based on the peak of the X-ray diffraction spectrum.
[0057] In this specification, unless otherwise specifically denied, the content of each component is expressed in mass % converted by oxide. Here, the so-called "oxide conversion" means that the amount of oxide of each component contained in the crystallized glass when the total mass of the oxide is set to 100 mass % is expressed in mass %. In this specification, A% to B% means more than A% and less than B%.
[0058] The crystallized glass used as the base material in the present invention is expressed in terms of mass % in terms of oxides:
[0059] The content of SiO2 component is 50.0% to 75.0%;
[0060] The content of Li2O component is 3.0% to 10.0%;
[0061] The content of Al2O3 component is 5.0% or more and less than 15.0%;
[0062] The content of B2O3 component is greater than 0% and less than 10.0%;
[0063] The content of P2O5 component is greater than 0% and less than 10.0%;
[0064] The mass ratio SiO2 / (B2O3+Li2O) is 3.0 to 10.0.
[0065] By having the above-mentioned main crystalline phase and composition, the glass transition temperature of the crystallized glass is lowered, the solubility of the raw materials is improved, and the production is easy. In addition, the obtained crystallized glass can be easily processed by 3D (Three Demensional) processing and the like.
[0066] Hereinafter, the composition range of each component constituting the crystallized glass serving as the base material in the present invention will be specifically described.
[0067] SiO2 component is a necessary component for constituting one or more selected from α-white silica and α-white silica solid solution. If the content of SiO2 component is 75.0% or less, excessive increase of viscosity or deterioration of solubility can be suppressed. In addition, if the content of SiO2 component is 50.0% or more, deterioration of resistance to devitrification can be suppressed.
[0068] The upper limit of the content of SiO2 component is preferably set to 75.0% or less, 74.0% or less, 73.0% or less, 72.0% or less, or 70.0% or less. In addition, the lower limit of the content of SiO2 component is preferably set to 50.0% or more, 55.0% or more, 58.0% or more, or 60.0% or more.
[0069] The Li2O component is a component that improves the meltability of raw glass. If the amount of the Li2O component is 3.0% or more, the effect of improving the meltability of raw glass can be obtained. In addition, by setting the amount of the Li2O component to 10.0% or less, the increase in the formation of lithium disilicate crystals can be suppressed. In addition, the Li2O component is a component related to chemical strengthening.
[0070] The lower limit of the amount of the Li2O component is preferably set to 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, or 5.5% or more. In addition, the upper limit of the amount of the Li2O component is preferably set to 10.0% or less, 9.0% or less, 8.5% or less, or 8.0% or less.
[0071] Al2O3 component is a component suitable for improving the mechanical strength of crystallized glass. If the content of Al2O3 component is set to less than 15.0%, the deterioration of solubility and resistance to devitrification can be suppressed. In addition, if the content of Al2O3 component is set to more than 5.0%, the reduction of mechanical strength can be suppressed.
[0072] Preferably, the upper limit of the content of the Al2O3 component is set to less than 15.0%, less than 14.5%, less than 14.0%, less than 13.5%, or less than 13.0%. In addition, the lower limit of the content of the Al2O3 component can be set to more than 5.0%, more than 5.5%, more than 5.8%, more than 6.0%, more than 6.5%, or more than 8.0%.
[0073] The B2O3 component is a component suitable for lowering the glass transition temperature of the crystallized glass. If the amount of the B2O3 component is set to 10.0% or less, a decrease in chemical durability can be suppressed.
[0074] The upper limit of the amount of the B2O3 component is preferably set to 10.0% or less, 8.0% or less, 7.0% or less, 5.0% or less, or 4.0% or less. In addition, the lower limit of the amount of the B2O3 component is preferably set to greater than 0%, 0.001% or more, 0.01% or more, 0.05% or more, 0.10% or more, or 0.30% or more.
[0075] The ZrO2 component is a component that can improve the mechanical strength. If the amount of the ZrO2 component is 10.0% or less, the deterioration of solubility can be suppressed.
[0076] The upper limit of the amount of the ZrO2 component is preferably set to 10.0% or less, 9.0% or less, 8.5% or less, or 8.0% or less. In addition, the lower limit of the amount of the ZrO2 component can be set to greater than 0%, 1.0% or more, 1.5% or more, or 2.0% or more.
[0077] If [Al2O3+ZrO2], which is the sum of the contents of Al2O3 and ZrO2, is high, the surface compressive stress will increase during strengthening. Preferably, the lower limit of [Al2O3+ZrO2] is set to 10.0% or more, 11.0% or more, 12.0% or more, or 13.0% or more.
[0078] On the other hand, by setting [Al2O3+ZrO2] to 22.0% or less, deterioration of solubility can be suppressed. Therefore, the upper limit of [Al2O3+ZrO2] is preferably set to 22.0% or less, 21.0% or less, 20.0% or less, or 19.0% or less.
[0079] The mass ratio SiO2 / (B2O3+Li2O) is preferably 3.0 to 10.0. By setting the mass ratio to 3.0 to 10.0, it is helpful to reduce the viscosity of the glass, make it easier to manufacture the glass, and increase the amount of alkaline ions that are ion-exchanged during chemical strengthening, thereby manufacturing the desired CS30 (compressive stress of 30 μm at a depth from the outermost surface) inorganic composition product.
[0080] Therefore, it is preferred that the lower limit of the mass ratio SiO2 / (B2O3+Li2O) is set to 3.0 or more, more preferably 3.5 or more, and even more preferably 4.64 or more. In addition, it is preferred that the upper limit of the mass ratio SiO2 / (B2O3+Li2O) is set to 10.0 or less, more preferably 9.5 or less, and even more preferably less than 8.6.
[0081] If the sum of the contents of SiO2, Li2O, Al2O3, and B2O3, i.e., [SiO2+Li2O+Al2O3+B2O3], is high, chemical strengthening is easy and a glass with high strength can be obtained. Therefore, it is preferred to set the lower limit of [SiO2+Li2O+Al2O3+B2O3] to 75.0% or more, 77.0% or more, 79.0% or more, 80.0% or more, 83.0% or more, or 85.0% or more.
[0082] The P2O5 component is an essential component added to function as a crystal nucleating agent for glass. By setting the amount of the P2O5 component to 10.0% or less, deterioration of the devitrification resistance of the glass and phase separation of the glass can be suppressed.
[0083] The upper limit of the amount of the P2O5 component is preferably set to 10.0% or less, 8.0% or less, 6.0% or less, 5.0% or less, or 4.0% or less. In addition, the lower limit of the amount of the P2O5 component can be greater than 0%, 0.5% or more, 1.0% or more, or 1.5% or more.
[0084] The K2O component is an arbitrary component that is involved in chemical strengthening when the content thereof is greater than 0%. The lower limit of the K2O component may be greater than 0%, 0.1% or more, 0.3% or more, or 0.5% or more.
[0085] In addition, by setting the K2O component to 5.0% or less, the precipitation of crystals can be promoted. Therefore, the upper limit of the K2O component can be preferably set to 5.0% or less, 4.0% or less, 3.5% or less, or 3.0% or less.
[0086] The Na2O component is an arbitrary component related to chemical strengthening when the content is greater than 0%. By setting the Na2O component to 4.0% or less, the desired crystalline phase can be easily obtained. The upper limit of the Na2O component is preferably 4.0% or less, 3.5% or less, more preferably 3.0% or less, and even more preferably 2.5% or less.
[0087] The MgO component, the CaO component, the SrO component, the BaO component, and the ZnO component are arbitrary components that improve low temperature melting property when the content thereof exceeds 0%, and may be contained within a range that does not impair the effects of the present invention.
[0088] Therefore, the upper limit of the MgO component can be preferably 4.0% or less, 3.5% or less, 3.0% or less, or 2.5% or less. In addition, the lower limit of the MgO component can be preferably greater than 0%, 0.3% or more, or 0.4% or more.
[0089] The upper limit of the CaO component can be preferably made 4.0% or less, 3.0% or less, 2.5% or less, or 2.0% or less.
[0090] The upper limit of the SrO component can be preferably made 4.0% or less, 3.0% or less, 2.5% or less, or 2.0% or less.
[0091] The upper limit of the BaO component can be preferably made 5.0% or less, 4.0% or less, 3.0% or less, 2.5% or less, or 2.0% or less.
[0092] The upper limit of the ZnO component can be preferably 10.0% or less, 9.0% or less, 8.5% or less, 8.0% or less, or 7.5% or less. The lower limit of the ZnO component can be preferably greater than 0%, 0.5% or more, or 1.0% or more.
[0093] The crystallized glass may or may not contain the Nb2O5 component, the Ta2O5 component, and the TiO2 component within a range that does not impair the effects of the present invention.
[0094] The Nb2O5 component is an arbitrary component that improves the mechanical strength of the crystallized glass when the content thereof is greater than 0%. The upper limit of the Nb2O5 component can be preferably 5.0% or less, 4.0% or less, 3.5% or less, or 3.0% or less.
[0095] The Ta2O5 component is an arbitrary component that improves the mechanical strength of the crystallized glass when the content thereof is greater than 0%. The upper limit of the Ta2O5 component can be preferably 6.0% or less, 5.5% or less, 5.0% or less, or 4.0% or less.
[0096] The TiO2 component is an arbitrary component that improves the chemical durability of the crystallized glass when the content is greater than 0%. The upper limit of the TiO2 component can be preferably less than 1.0%, less than 0.8%, less than 0.5%, or less than 0.1%.
[0097] In addition, the crystallized glass may contain or not contain La2O3, Gd2O3, Y2O3, WO3, TeO2, and Bi2O3, respectively, within the range that does not impair the effect of the present invention. The blending amount may be set to 0% to 2.0%, 0% to less than 2.0%, or 0% to 1.0%.
[0098] Further in the crystallized glass, other components not described above may be included or not included within the scope that does not damage the characteristics of the crystallized glass of the present invention. For example, metal components (including metal oxides of these metal components) such as Yb, Lu, V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, etc.
[0099] Sb2O3 may also be contained as a clarifier for the glass. On the other hand, by setting the Sb2O3 component to 3.0% or less, the transmittance in the short wavelength region of the visible light region can be suppressed from being deteriorated. Therefore, the upper limit of the Sb2O3 component is preferably 3.0% or less, more preferably 2.0% or less, still more preferably 1.0% or less, and further preferably 0.6% or less.
[0100] In addition, as a clarifier of the glass, in addition to the Sb2O3 component, a SnO2 component, a CeO2 component, an As2O3 component, and one or more selected from the group consisting of F, NOx, and SOx may or may not be included. Among them, the upper limit of the content of the clarifier is preferably 2.0% or less, more preferably 1.0% or less, and most preferably 0.6% or less.
[0101] On the other hand, since each of Pb, Th, Tl, Os, Be, Cl and Se has a tendency to be restricted in use as a harmful chemical substance in recent years, it is preferable that these components are not substantially contained.
[0102] The compressive stress (CS [MPa]) of the compressive stress layer of the inorganic composition product of the present invention is preferably 550 MPa or more, more preferably 600 MPa or more, and even more preferably 700 MPa or more. The upper limit is, for example, 1400 MPa or less, 1300 MPa or less, 1200 MPa or less, or 1100 MPa or less. By having such a compressive stress value, the development of cracks can be suppressed, thereby improving the mechanical strength.
[0103] The inorganic composition product of the present invention has a compressive stress (CS30 [MPa]) of 120 MPa to 320 MPa at a depth of 30 μm from the outermost surface. When CS30 is 120 MPa to 320 MPa, it becomes less likely to break when dropped onto a rough surface. CS30 is preferably 130 MPa to 310 MPa, and more preferably 140 MPa to 300 MPa.
[0104] The central tensile stress (CT [MPa]) is an index of the degree of glass strengthening achieved by chemical strengthening. If the CT value is high, the fragments when the glass breaks become smaller and tend to break into small fragments. Therefore, for the impact resistance of the glass, the central tensile stress (CT [MPa]) is preferably more than 80MPa, more preferably more than 90MPa, and more preferably more than 95MPa. The upper limit is, for example, less than 160MPa, less than 155MPa, less than 150MPa or less than 130MPa. By having such a central tensile stress, the desired strengthened crystallized glass achieved by chemical strengthening can be obtained.
[0105] The thickness of the compressive stress layer (DOLzero [μm]) also depends on the thickness of the crystallized glass, so there is no limit. For example, when the thickness of the crystallized glass substrate is 0.7 mm, the lower limit of the thickness of the compressive stress layer can be set to more than 70 μm or more than 100 μm, and the upper limit can be set to less than 180 μm or less than 160 μm.
[0106] When crystallized glass is used as the substrate, the lower limit of the thickness of the substrate is preferably 0.1 mm or more, more preferably 0.3 mm or more, even more preferably 0.4 mm or more, and further preferably 0.5 mm or more, and the upper limit of the thickness of the substrate is preferably 2.0 mm or less, more preferably 1.5 mm or less, even more preferably 1.1 mm or less, further preferably 1.0 mm or less, even more preferably 0.9 mm or less, and yet further preferably 0.8 mm or less.
[0107] Crystallized glass can be produced by the following method: that is, raw materials are uniformly mixed so that each component is within a predetermined content range, melted and molded to produce blank glass, and then the blank glass is crystallized to produce crystallized glass.
[0108] The glass transition temperature (Tg) of the crystallized glass is preferably 610° C. or lower, more preferably 600° C. or lower, and still more preferably 590° C. or lower.
[0109] The heat treatment for crystallization may be performed in one step or two steps.
[0110] In the two-step heat treatment, heat treatment is first performed at a first temperature to perform a nucleation step, and after the nucleation step, heat treatment is performed at a second temperature higher than the nucleation step to perform a crystal growth step.
[0111] The first temperature of the two-step heat treatment is preferably 450 to 750° C., more preferably 500 to 720° C., and even more preferably 550 to 680° C. The holding time at the first temperature is preferably 30 to 2000 minutes, and more preferably 180 to 1440 minutes.
[0112] The second temperature of the two-step heat treatment is preferably 550° C. to 850° C., more preferably 600° C. to 800° C. The holding time at the second temperature is preferably 30 minutes to 600 minutes, more preferably 60 minutes to 400 minutes.
[0113] In the one-stage heat treatment, the nucleation step and the crystal growth step are performed continuously at one stage of temperature. Generally, the temperature is raised to a predetermined heat treatment temperature, and after reaching the heat treatment temperature, the temperature is maintained for a certain period of time, and then the temperature is lowered.
[0114] When performing a one-step heat treatment, the heat treatment temperature is preferably 600 to 800° C., more preferably 630 to 770° C. In addition, the holding time at the heat treatment temperature is preferably 30 to 500 minutes, more preferably 60 to 400 minutes.
[0115] As a method for forming a compressive stress layer in an inorganic composition product, there is a chemical strengthening method, for example, a compressive stress layer is formed on the surface layer by exchanging an alkaline component existing in the surface layer of the crystallized glass with an alkaline component having an ion radius larger than that of the alkaline component. In addition, there is a thermal strengthening method of heating the crystallized glass and then quenching it; and an ion implantation method of implanting ions into the surface layer of the crystallized glass.
[0116] The inorganic composition product of the present invention can be produced, for example, by the following chemical strengthening method.
[0117] The crystallized glass is contacted with or immersed in a salt containing potassium, sodium and lithium, such as a mixed salt of potassium nitrate (KNO3), sodium nitrate (NaNO3) and lithium nitrate (LiNO3) or a molten salt of a composite salt. The contact or immersion treatment in the molten salt can be performed in one stage or in two stages.
[0118] In the case of a two-stage treatment, for example, in the first stage, the mixture is contacted or immersed in a mixed salt of potassium and sodium or a sodium salt or a mixed salt of potassium, sodium and lithium heated at 350° C. to 550° C. for 1 minute to 1440 minutes, preferably 15 minutes to 500 minutes, and more preferably 30 minutes to 300 minutes. Then, in the second stage, the mixture is contacted or immersed in a potassium salt, a mixed salt of potassium and sodium, a mixed salt of potassium and lithium, or a mixed salt of potassium, sodium and lithium heated at 350° C. to 550° C. for 1 minute to 1440 minutes, preferably 60 minutes to 600 minutes.
[0119] In the case of a two-stage treatment, for example, the first stage treatment is preferably carried out using a single bath or a mixed bath of potassium (KNO3), sodium (NaNO3) or lithium (LiNO3), and the second stage treatment is preferably carried out using a molten salt containing a salt of potassium, sodium and lithium, such as a mixed salt or a composite salt of potassium nitrate (KNO3), sodium nitrate (NaNO3) and lithium nitrate (LiNO3).
[0120] In the case of performing chemical strengthening treatment in one stage, for example, contact or immersion in a mixed salt containing potassium and sodium or a mixed salt containing potassium, sodium and lithium, a mixed salt containing sodium, a mixed salt containing sodium and lithium (a mixed salt containing potassium and / or sodium and / or lithium) heated at 350°C to 550°C is performed for 1 minute to 1440 minutes, preferably 30 minutes to 500 minutes.
[0121] Example
[0122] Example 1, Comparative Example 1
[0123] 1. Production of inorganic composition products
[0124] As raw materials for each component of crystallized glass, corresponding raw materials of oxides, hydroxides, carbonates, nitrates, fluorides, chlorides, metaphosphate compounds, etc. are selected, and these raw materials are weighed and uniformly mixed in a manner to have the composition shown in Table 1.
[0125] Next, the mixed raw materials are put into a platinum crucible and melted in an electric furnace at 1300°C to 1600°C for 2 hours to 24 hours. Then, the molten glass is stirred and homogenized, and the temperature is lowered to 1000°C to 1450°C and cast into a mold, and slowly cooled to produce a blank glass. The obtained blank glass is heated under the crystallization conditions of the nucleation step and the crystal growth step described in Table 1 to produce a crystallized glass.
[0126] The crystalline phase of the crystallized glass is determined by the angle of the peak presented in the X-ray diffraction spectrum using an X-ray diffraction analysis device (manufactured by Bruker; D8Discover). The X-ray diffraction spectrum of Example 1 is confirmed. Since the main peaks (peaks with the highest intensity and the largest peak area) are all seen at positions corresponding to the peak spectrum of α-white silica and / or α-white silica solid solution, it is determined that all α-white silica and / or α-white silica solid solution are precipitated as the main crystalline phase. Comparative Example 1 is an X-ray diffraction analysis device (manufactured by Bruker; D8 Discover) and the peaks of α-white silica and α-white silica solid solution are not confirmed. Therefore, after confirming the lattice image (lattice image) achieved by the electron diffraction image, the crystalline phase is confirmed by EDX (Energy dispersive X-ray spectroscopy; Energy dispersive X-ray spectroscopy). As a result, it was confirmed that the crystal phases of the glass of Comparative Example 1 were MgAl 2 O 4 and MgTi 2 O 4 .
[0127] The glass transition point (TG) of the glass before crystallization of Example 1 was measured in accordance with Japan Optical Glass Industry Association Standard JOGIS08-2019 “Measurement method of thermal expansion of optical glass”.
[0128] The crystallized glass prepared according to Example 1 and Comparative Example 1 was cut and ground, and then ground parallel to the plane in a manner such that the thickness became the material thickness (substrate thickness) shown in Table 2 and Table 3, thereby obtaining a crystallized glass substrate. The crystallized glass substrate was used as a mother material to obtain a chemically strengthened crystallized glass substrate.
[0129] Examples 1-1 to 1-9 use the crystallized glass of Example 1 and perform two-stage strengthening under the strengthening conditions shown in Tables 2 and 3. Specifically, in Examples 1-1 to 1-9, a salt bath containing LiNO3 is used in the first stage and / or the second stage to strengthen the substrate.
[0130] In Comparative Example 1-1, the crystallized glass of Comparative Example 1 was used, and in Comparative Example 2-1, the crystallized glass of Example 1 was used, and two-step strengthening was performed under the strengthening conditions shown in Table 3.
[0131]
Table 1
[0132]
[0133] 2. Evaluation of inorganic composition products
[0134] The following properties were measured for the obtained tempered crystallized glass substrate, and a drop test was performed. The results are shown in Tables 2 and 3.
[0135] (1) Stress measurement
[0136] The compressive stress value (CS) of the outermost surface was measured using a glass surface stress meter FSM-6000LE series manufactured by Orihara Seisakusho Co., Ltd., and a light source with a wavelength of 365 nm was used as the light source of the measuring machine.
[0137] The compressive stress (CS30) at a depth of 30 μm from the outermost surface was measured using an SLP-1000 series, and a light source with a wavelength of 518 nm was used as the light source of the measuring machine.
[0138] The refractive index used for the measurement of CS and CS30 is the value of the refractive index at 365nm and 518nm. In addition, the refractive index value is calculated using the quadratic approximation formula based on the V-block method specified in JIS B 7071-2:2018, from the measured values of the refractive index at the wavelengths of C-ray, d-ray, F-ray, and g-ray.
[0139] The photoelastic constants used for the measurement of CS and CS30 are the values of the photoelastic constants at 365nm and 518nm. In addition, the photoelastic constants are calculated using the quadratic approximation formula from the measured values of the photoelastic constants at wavelengths of 435.8nm, 546.1nm, and 643.9nm. In Example 1, as the photoelastic constant, 31.3 was used at 365nm, and 30.1 was used at 518nm. In Comparative Example 1, as the photoelastic constant, 28.7 was used at 365nm, and 27.8 was used at 518nm.
[0140] The photoelastic constant (β) is obtained by grinding the sample into a disk shape with a diameter of 25 mm and a thickness of 8 mm, applying a compressive load in a predetermined direction, measuring the optical path difference generated at the center of the glass, and using the relational mathematical formula δ = β.dF. In this relational mathematical formula, the optical path difference is expressed as δ (nm), the thickness of the glass is expressed as d (mm), and the stress is expressed as F (MPa).
[0141] The depth DOLzero (μm) and the central tensile stress (CT) of the compressive stress layer when the compressive stress is 0 MPa were measured using a scattered light photoelastic stress meter SLP-1000. A light source with a wavelength of 518 nm was used as the measurement light source.
[0142] The numerical value of the refractive index at a wavelength of 518 nm is calculated using a quadratic approximation from measured values of the refractive index at wavelengths of C-rays, d-rays, F-rays, and g-rays according to the V-block method specified in JIS B 7071-2:2018.
[0143] The photoelastic constant at a wavelength of 518 nm used for DOLzero and CT measurements can be calculated using a quadratic approximation from the measured values of the photoelastic constants at wavelengths of 435.8 nm, 546.1 nm, and 643.9 nm. In Example 1, 30.1 was used. In Comparative Example 1, 27.8 was used as the photoelastic constant.
[0144] (2) Substrate drop test
[0145] A drop test was performed using sandpaper in the following manner. The drop test simulated dropping onto asphalt.
[0146] As a drop test sample, a glass substrate of the same size is attached to the inorganic composition product (156mm long × 71mm wide) to make a drop test sample. In addition, the weight of the drop test samples is all set to 46g. Sandpaper with a roughness of #80 is applied to the stainless steel base, and the drop test sample is dropped onto the base from a height of 20cm from the base in a manner that the inorganic composition product is below. After falling, as long as the inorganic composition product is not broken, the height is increased by 5cm, and the height is repeatedly increased and dropped until it breaks. The test is implemented 3 times (n1 to n3), and the average height of the broken inorganic composition products from n1 to n3 is calculated. The results are shown in Tables 2 to 3.
[0147]
Table 2
[0148]
[0149]
Table 3
[0150]
[0151] As described above, several embodiments and / or examples of the present invention have been described in detail, but those skilled in the art can easily make many changes to the embodiments and / or examples without departing from the novel teachings and effects of the present invention. Therefore, these many changes are included in the scope of the present invention.
[0152] The present invention cites all the contents of the documents described in this specification and the applications serving as the basis for priority under the Paris Convention.
Claims
1. An inorganic composition product, which is formed by strengthening crystallized glass, wherein the crystallized glass contains one or more selected from α-white silica and α-white silica solid solution as the main crystalline phase; in terms of mass % converted into oxides: The content of SiO2 component is 50.0% to 75.0%; The content of Li2O component is 3.0% to 10.0%; The content of Al2O3 component is 5.0% or more and less than 15.0%; The content of B2O3 component is greater than 0% and less than 10.0%; The content of P2O5 component is greater than 0% and less than 10.0%; and The mass ratio SiO2 / (B2O3+Li2O) is 3.0 to 10.0, and The inorganic composition product has a compressive stress layer on the surface, and the central tensile stress (CT) of the compressive stress layer is 80 MPa to 160 MPa.
2. The inorganic composition product according to claim 1, wherein: The crystallized glass is calculated in terms of mass % of oxides: The content of ZrO2 component is greater than 0% and less than 10.0%; The total content of Al2O3 and ZrO2 components is 10.0% or more.
3. The inorganic composition product according to claim 1 or 2, wherein: The crystallized glass is calculated in terms of mass % of oxides: The content of K2O component is 0% to 5.0%.
4. The inorganic composition product according to claim 1 or 2, wherein: The crystallized glass is calculated in terms of mass % of oxides: The content of Na2O component is 0% to 4.0%; The content of MgO component is 0% to 4.0%; The content of CaO component is 0% to 4.0%; The content of SrO component is 0% to 4.0%; The content of BaO component is 0% to 5.0%; The content of ZnO component is 0% to 10.0%; The content of Sb2O3 component is 0% to 3.0%.
5. The inorganic composition product according to claim 1 or 2, wherein: The crystallized glass is calculated in terms of mass % of oxides: The content of Nb2O5 component is 0% to 5.0%; The content of Ta2O5 component is 0% to 6.0%; The content of the TiO2 component is 0% or more and less than 1.0%.
6. The inorganic composition product according to claim 1 or 2, wherein: The glass transition temperature (Tg) of the crystallized glass before crystallization is 610° C. or less.
7. The inorganic composition product according to claim 1 or 2, wherein: The crystallized glass is chemically strengthened by using a salt bath containing lithium.
Citation Information
Patent Citations
Inorganic composition article
JP2008254984A